2017
DOI: 10.1186/s13256-017-1300-9
|View full text |Cite
|
Sign up to set email alerts
|

BK polyomavirus nephropathy in two kidney transplant patients with distinct diagnostic strategies for BK virus and similar clinical outcomes: two case reports

Abstract: BackgroundBK polyomavirus-associated nephropathy is an important cause of post-transplantation renal failure. We present two cases of BK polyomavirus-associated nephropathy who were submitted to contrasting strategies of clinical follow-up to BK polyomavirus reactivation, but progressed to a similar final outcome.Case presentationCase 1 is a 37-year-old white man whose graft had never presented a good glomerular filtration rate function, with episodes of tacrolimus nephrotoxicity, and no urinary monitoring for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In our study, the finding of a NCCR identical to the prototypic NCCR BKPyV strain, both in plasma and in urine samples, suggested that other factors, such as the immune‐competence of the host and the level of immunosuppression might have had a role in determining the poor outcome of PyVAN. The attempt to significantly reduce the level of immunosuppression as indicated by the immediate, complete weaning of Mycophenolic acid, and gradual tapering and subsequent weaning of Tacrolimus failed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, the finding of a NCCR identical to the prototypic NCCR BKPyV strain, both in plasma and in urine samples, suggested that other factors, such as the immune‐competence of the host and the level of immunosuppression might have had a role in determining the poor outcome of PyVAN. The attempt to significantly reduce the level of immunosuppression as indicated by the immediate, complete weaning of Mycophenolic acid, and gradual tapering and subsequent weaning of Tacrolimus failed.…”
Section: Discussionmentioning
confidence: 99%
“…Reactivation can occur in the context of an immunosuppression state after kidney transplantation. BKPyV replication within the renal epithelial tubular cells causes inflammation that can progress to polyomavirus‐associated nephropathy (PyVAN) and eventually graft loss . The present study describes the case of a kidney transplant patient who developed 7 months after transplant a PyVAN because of a high replication rate of BKPyV that brought to kidney failure.…”
Section: Introductionmentioning
confidence: 98%
“…When the BK virus reactivates in immunocompromised hosts (such as HCT or solid organ transplant recipients) or immunocompromised (such as AIDS patients), it can lead to severe clinical diseases. For example, BKV reactivation can lead to polyomavirus-associated nephropathy in kidney transplant patients [4,5]. Additionally, BKV reactivation may result in renal failure and allograft failure in kidney transplant patients.…”
Section: Introductionmentioning
confidence: 99%
“…About 10% of kidney transplant patients develop BKPyV-associated nephropathy, with loss of graft function in up to 50% of the cases. 23 …”
Section: History Of Polyomavirus and Merkel Cell Polyomavirusmentioning
confidence: 99%